الزيت واستخداماته في ماري (في بداية الألف الثاني قبل الميلاد) - شحود, أحمد (Latakia University Journal - Arts and Humanities Sciences Series, 2016)
هذا البحث يقدم عرضاً لمادة الزيت في القرن الثامن عشر قبل الميلاد في منطقة بلاد الرافدين وبالتحديد في مملكة ماري وذلك من خلال نصوص أرشيف هذه المملكة. فالزيت لعب دوراً هاماً في علاقات هذ المملكة مع الممالك المجاورة كمملكة يمحاض (حلب), كما قدم مثالاً لمعالجة المادة الأولية وعملية استخراج الزيت إضافةً إلى استخداماته في الحياة اليومية عند سكان هذه المملكة بخاصةٍ تواجده كمادة أساسية في وجبات الملك. كما ويقدم البحث عرضاً لمادة العطر ومادة المراهم المستخرجة من الزيت واستخدام هذه المواد إضافةً لأنواع العطور والمراهم المستخرجة من أنواع مختلفةٍ من الزيوت. This paper studies oil in 18th Century B.C. in Mesopotamia, especially in the Kingdom of Mari, through ananalysis of the texts in the archive of that kingdom. Oil played an important role in that kingdom's relationships with nearby kingdoms, such as Yamhhad (Aleppo). Oil also presented an example the processing of raw material as well as the process of oil distilment. It also points to its uses in daily life by the citizens of that Kingdom, especially its presence as an essential element in the king's meals. The paper also presents an idea about fragrance and ointment distilled from different kinds of oil to be used as medical drugs.